2019
DOI: 10.1007/s10554-019-01737-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantitative flow ratio and fractional flow reserve with myocardial perfusion scintigraphy and cardiovascular magnetic resonance as reference standard. A Dan-NICAD substudy

Abstract: Quantitative flow ratio (QFR) and fractional flow reserve (FFR) have not yet been compared head to head with perfusion imaging as reference for myocardial ischemia. We aimed to compare the diagnostic accuracy of QFR and FFR with myocardial perfusion scintigraphy (MPS) or cardiovascular magnetic resonance (CMR) as reference. This study is a predefined post hoc analysis of the Dan-NICAD study (NCT02264717). Patients with suspected coronary artery disease by coronary computed tomography angiography (CCTA) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
11
1
3
Order By: Relevance
“…One of the main reasons is the burden of disease which is reflected by the different QFR-values. Our study had a mean QFR of 0.94, which is in contrast to the study of Sejr-Hansen and colleagues with a mean QFR of 0.84 [ 9 ]. Another reason might be the selection process of patients for the study.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…One of the main reasons is the burden of disease which is reflected by the different QFR-values. Our study had a mean QFR of 0.94, which is in contrast to the study of Sejr-Hansen and colleagues with a mean QFR of 0.84 [ 9 ]. Another reason might be the selection process of patients for the study.…”
Section: Discussioncontrasting
confidence: 90%
“…The recently published MR-INFORM trial demonstrated the use of myocardial- perfusion cardiovascular MRI in guiding initial management of patient care was noninferior to the use of invasive coronary angiography combined with FFR with respect to the primary outcome of major adverse cardiac events at 1 year [ 22 ]. Until now only one study has investigated the association between stress MRI and cQFR [ 9 ]. Interestingly, there is an obvious difference between the two studies regarding sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative flow ratio (QFR) is a novel method to assess hemodynamic relevance of coronary lesions based on a three-dimensional vessel reconstruction and estimation of its contrast media flow velocity [ 1 , 2 , 3 , 4 ]. In contrast to wire based methods such as fractional flow reserve (FFR) or instantaneous wave-free ratio (iFR), QFR does not require pressure wires or drug-induced hyperemia [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…“Comparison of quantitative flow ratio and fractional flow reserve with myocardial perfusion scintigraphy and cardiovascular magnetic resonance as reference standard. A Dan-NICAD substudy” by Sejr-Hansen et al [ 5 ] was downloaded 1087 times. These workers compared FFR CT and CT perfusion (CTP) to FFR.…”
mentioning
confidence: 99%